Effect of treatment with nasal IgA on the incidence of infectious disease in world-class canoeists - Lindberg, K.; Berglund, B. (International Journal of Sports Medicine, 1996)
Earlier studies of endurance athletes have shown decreased levels of secretory IgA and an increased frequency of upper respiratory tract (URT) infections after periods of hard training. In this study, 14 world-class canoeists were studied during very hard physical training, after lower-intensity training combined with 17 days of treatment with nasal IgA, and during low intensity training off-season. The ELISA method was used to determine IgA in nasopharyngeal (nph) secretions and saliva (s). The results demonstrated unchanged nph secretions before, during and after IgA treatment (IgAbulin, Immuno AG, Vienna, Austria). Saliva Ig-A increased significantly from a median value of 147 micrograms/ml (range 37-634) to 410 micrograms/ml (range 82-974) (p < 0.05) during treatment. Thereafter, s-IgA decreased to 244 micrograms/ml (range 85-689) off-season. A control group of untrained students showed similar nph IgA to that of the elite canoeists. The athletes receiving nasal IgA showed no signs of URT and were considered healthy during 14.5 days out of 17 days of treatment as compared to 12.3 healthy days out of 17 days in the control group. In summary there was no significant decrease in IgA in untreated elite canoeists as compared to untrained controls. Nasal IgA treatment increased the IgA level in saliva only, but no significant decrease in URT symptoms was seen during the IgA treatment period.